Evaluation and Research on Accessibility and Path Redundancy of Shanghai Urban Rail Transit Network - ZHANG Qi (Chengshi guidao jiaotong yanjiu)
[Objective] To better measure the performance level of urban rail transit networks under both normal and abnormal conditions, it is essential to evaluate the accessibility and path redundancy of urban rail transit networks. [Method] Taking the urban rail transit network in Shanghai as an example, calculation and analysis of accessibility and path redundancy are conducted. In terms of accessibility, evaluation indicators are established based on the shortest path travel time considering the interchange time, to calculate the reachable area and the scale of the served population under different travel time scenarios. While in terms of path redundancy, the path redundancy is characterized by the number of effective paths that take into account path selection behavior preferences. [Result & Conclusion] The urban rail transit network in Shanghai demonstrates relatively good accessibility, with approximately 50% and 95% of trips being completed within 50 minutes and 90 minutes, respectively. Only a small number of OD (origin-destination) pairs exhibit higher path redundancy. The ratio of travel time to the number of effective paths is used to characterize the OD pair ability against disturbances, which approximately follows a skewed normal distribution. OD pairs located at the tail of the distribution with higher travel demand show greater vulnerability, requiring special attention in future planning and design.